Influence of the episiotomy versus the perineal laceration on the normalization of the sexual relations in the postpartum - Juan Miguel Martínez Galiano (Fundación para el Desarrollo de la Enfermería, 2009)
During the process of pregnancy, childbirth and puerperium the majority of the women experience a decrease of the frequency of the sexual relations, of the libido and of the pleasure that provides these relations to them. The presence of the episiotomy does that the normalization of the sexual relations is late. There does no seem to be relation between the type of childbirth (vaginal or caesarean) and the sexual function. Certain factors influence the resumption of the sexual relations.Objectives: To determine the time that the women are late in the sexual relations restart after the childbirth vaginal route, to value that repercussion has the episiotomy and the perineal laceration on the regularization of the sexual activity of the women, to know that type of sexual relation is kept of beginning after the childbirth, to detect factors that influence the normalization of the sexual relations after the childbirth. Methodology: Observational, analytical prospective Study in the sanitary area of the Hospital San Juan de la Cruz de Úbeda, women who give birth in the Hospital San Juan de la Cruz de Úbeda (Jaen) between the months of Julio and December, 2008, realizes telephonic interview to 60 days of the childbirth. There will be in use a questionnaire of proper elaboration. Discussion: Sex partner benefits physical, psychological and social, according to various studies, these relationships are affected by the process of pregnancy, childbirth and puerperium, a policy of selective episiotomy that recommends all the scientific evidence favors normalization of sexual activity. It is possible that we are certain biases such as non-response bias in classification, etc. but methodological tools to deal with its impact on the results are minimized.